IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MASYARAKAT DIGITAL DI KALANGAN REMAJA - Naifa Zayyan, Talitha (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
Character education is an effort to instill good values in individuals, to do positive things in daily life, such as morals and ethics. However, currently due to the development of digital technology which greatly affects everyone, teenagers lack character education, such as bullying through social media, providing false information and teenagers can be affected by other dangers that they get from uncontrolled digital technology. Therefore, this study is used to identify how the implementation of character education can be carried out in a digital society, especially among teenagers. This study uses a qualitative method, which is a method used in collecting data through relevant supporting reference sources. This research provides the results that character education can be carried out if it gets support from several components or elements, such as parents, schools and society itself which currently due to technological developments have changed into a generation of digital society era.